Are general movements at 3-5 months correlated and compatible with the Bayley-III at 1,5-2 years age? - Kahraman, Aysu; Livanelioğlu, Ayşe; Kara, Özgün Kaya; Yurdakök, Murat (The Turkish Journal of Pediatrics, 2020)
Since early intervention is important in risky infants, it is also important to identify developmental problem as early as possible. There are various assessment methods for this. One of them is the General movements assessment (GMs), and the other one is the Bayley Scales of Infants and Toddler Developmental, third edition (Bayley-III). The present study aimed to compare the neurodevelopmental outcomes and Bayley-III scores at the age of 1.5-2 years with fidgety GMs. One hundred and twenty-six infants (57 females, 69 males) were assessed by the GMs at the corrected 3-5 months and also by the Bayley-III at the age of 1.5-2 years. According to the GMs, 21 infants exhibited the absence of fidgety movements, six infants exhibited abnormal fidgety movements, and 99 infants exhibited normal fidgety movements. According to the Bayley-III, 19 infants` motor scores, 13 infants` language scores, and 18 infants` cognitive scores were low (-2SD). Various neurodevelopmental problems were identified in 25.4% of the infants. As a result, although in the present study the Bayley-III underestimates the rates of motor impairment, it was found to be moderately compatible with the GMs at 3-5 months (r= 0.4, p < 0.001). However, the GMs were better than the Bayley-III in predicting neurodevelopmental outcomes at the age of 1.5-2. Although the Bayley-III and GMs may be valuable tools for estimating the later outcomes of infants, care should be taken while interpreting their results.
Keywords: Bayley-3 infants and toddler developmental; fidgety movements; neurodevelopmental outcome